Autoecology of Ceratium furca and Chaetoceros didymus as potential harmful algal blooms in tourism and aquaculture sites at Teluk Pandan Bay, Lampung, Indonesia - QADAR HASANI; MAULID WAHID YUSUP; RACHMAD CAESARIO; DAVID JULIAN; AHMAD MUHTADI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Hasani Q, Yusup MW, Caesario R, Julian D, Muhtadi A. 2022. Autoecology of Ceratium furca and Chaetoceros didymus as potential harmful algal blooms in tourism and aquaculture sites at Teluk Pandan Bay, Lampung, Indonesia. Biodiversitas 23: 5670-5680. Harmful algal blooms (HABs) phenomenon has been observed around tourism and aquaculture sites in Teluk Pandan Waters, Lampung Bay. The dominant potential HABs found in Teluk Pandan waters were Ceratium furca and Chaetoceros didymus. This study aimed to analyze the relationship between the environmental physicochemical factors and the abundance of C. furca and C. didymus as potential HABs. Phytoplankton samples were collected from four stations (Hurun Bay, Sidodadi Coastal Waters, Sari Ringgung Beach and Cikunyinyi Bay) during May-August 2022. Physical parameters (temperature, depth, brightness, current velocity and salinity), as well as chemical parameters (dissolved oxygen, pH, phosphate, nitrite, nitrate and ammonia) were all measured in conjunction with phytoplankton sampling. Canonical correlation analysis and multiple regression were used to predict the effect of environmental parameters on phytoplankton density. Blooms of C. furca were found with the highest density at 5.417×106 cells/L in Cikunyiyi Bay, while C. didymus predominated in Hurun Bay (2.890×104 cells/L), Sidodadi Coastal Waters (3.923×104 cells/L) and Sari Ringgung Beach (3.531×104 cells/L). The main factors influencing the increase in C. furca population at Cikunyinyi Bay were pH, phosphate and nitrate. The increase in C. didymus population at Sidodadi Coastal Waters was affected by phosphate, nitrate and nitrite, while phosphate and nitrate influenced the increase in C. didymus population at Sari Ringgung Beach. Potentially HABs density was found to be higher near intensive shrimp farming sites. The use of fertilizer and artificial feed in high quantities is thought to be responsible for increased water eutrophication. Periodic monitoring and consistent determination of environmental carrying capacity for intensive shrimp farming activities are required to control HABs and ensure the sustainability of aquaculture and tourism activities in Teluk Pandan Waters.